Improved Biodistribution and Extended Serum Half-Life of a Bacteriophage Endolysin by Albumin Binding Domain Fusion - Seijsing, Johan; Sobieraj, Anna M.; Keller, Nadia; Shen, Yang; Zinkernagel, Annelies S.; Loessner, Martin J.; Schmelcher, Mathias (Frontiers in Microbiology, 2018)
The increasing number of multidrug-resistant bacteria intensifies the need to develop new antimicrobial agents. Endolysins are bacteriophage-derived enzymes that degrade the bacterial cell wall and hold promise as a new class of highly specific and versatile antimicrobials. One major limitation to the therapeutic use of endolysins is their often short serum circulation half-life, mostly due to kidney excretion and lysosomal degradation. One strategy to increase the half-life of protein drugs is fusion to the albumin-binding domain (ABD). By high-affinity binding to serum albumin, ABD creates a complex with large hydrodynamic volume, reducing kidney excretion and lysosomal degradation. The aim of this study was to investigate the in vitro antibacterial activity and in vivo biodistribution and half-life of an engineered variant of the Staphylococcus aureus phage endolysin LysK. The ABD sequence was introduced at different positions within the enzyme, and lytic activity of each variant was determined in vitro and ex vivo in human serum. Half-life and biodistribution were assessed in vivo by intravenous injection of europium-labeled proteins into C57BL/6 wild-type mice. Our data demonstrates that fusion of the endolysin to ABD improves its serum circulation half-life and reduces its deposition in the kidneys in vivo. The most active construct reduced S. aureus counts in human serum ex vivo by 3 logs within 60 minutes. We conclude that ABD fusions provide an effective strategy to extend the half-life of antibacterial enzymes, supporting their therapeutic potential for treatment of systemic bacterial infections.